Mutations in both SAMD9 and SLC19A2 genes caused complex phenotypes characterized by recurrent infection, dysphagia and profound deafness - a case report for dual diagnosis - Yan Zhang; Yi Zhang; Victor Wei Zhang; Chunyi Zhang; Hongke Ding; Aihua Yin (BMC, 2019)
Abstract Background Phenotypic difference is general in Mendelian disease. Due to the extremely low incidence for a single disease, phenotype spectrum needs to be expanded. Meanwhile, earlier knowledge says patients who suffered from two kinds of different Mendelian disease are very rare. Case presentation We describe a case of neonatal male with genital anomalies, growth delay, skin hyperpigmentation, chronic lung disease with recurrent infection, anemia, and severe deafness. Without any clear etiology after routine workflow, whole exome sequencing was carried on. A pathogenic de novo SAMD9 mutation and compound heterozygous likely-pathogenic variants in SLC19A2 were identified. Some symptoms were improved after the patient was treated with vitamin B1. Unfortunately, the boy died from sepsis and multiple organ failure before 1 year old. Conclusion Combining the phenotype and clinical progress of treatment, we report that it is the first case of a patient with both MIRAGE syndrome and TRMA syndrome.